Rethinking Australian public relations history in the mid-20th century. Issue 1 (August 2016) - Fitch, Kate
This article investigates the development of public relations in Australia and addresses calls to reconceptualise Australian public relations history. It presents the findings from an analysis of newspaper articles and industry newsletters in the 1940s and 1950s. These findings confirm the term public relations was in common use in Australia earlier than is widely accepted and not confined to either military information campaigns during the war or the corporate sector in the post-war period, but was used by government and public institutions and had increasing prominence through industry associations in the manufacturing sector and in social justice and advocacy campaigns. The study highlights four themes – war and post-war work, non-profit public relations, gender, and media and related industries – that enable new perspectives on Australian public relations history and historiography to be developed.